DOES E-LEARNING IMPROVE LEARNING OUTCOMES IN ICT-BASED COURSES? AN EXPERIMENTAL APPROACH - Ade Fricticarani; Mohamad Bayi Tabrani; Siti Aspariah; Babay Suhendri; Mulya Tiara Fauziah (Jurnal Bisnis Digital, 2026)
The integration of digital technologies in higher education has accelerated the adoption of e-learning, particularly in Information and Communication Technology (ICT)-based courses. However, evidence regarding its effectiveness in improving student learning outcomes remains inconclusive. This study aimed to examine the effect of e-learning on learning outcomes in ICT-based courses using an experimental approach. This research employed a quantitative experimental method with a one-group pretest–posttest design. The participants were 43 undergraduate students from the Information Technology Study Program selected through purposive sampling. Data were collected using pretest and posttest achievement tests and analyzed through descriptive statistics, Shapiro–Wilk normality testing, paired sample t-test, N-Gain analysis, and Cohen’s d effect size. The results revealed a significant improvement in students’ learning outcomes after the implementation of e-learning. Statistical analysis indicated a significant difference between pretest and posttest scores, supported by a moderate N-Gain score and a large effect size. These findings suggest that e-learning effectively improves students’ learning outcomes in ICT-based courses and offers both academic and practical benefits in technology-oriented learning environments. Therefore, well-designed e-learning systems should be further integrated into higher education, particularly in digitally aligned disciplines.